What music teacher will I be? A case study on the teaching philosophies of final-year pre-service Swedish music teachers. - Mateos-Moreno, Daniel (Federal University of Goiás, 2022)
Written teaching philosophies are a common part of applications for music teaching positions and a pivotal exercise for pre-service teacher development. However, their contents are not often addressed in the music education research literature. Using a case study of last-year pre-service music teachers at a Swedish university, I explore these statements to uncover their beliefs about practicing the music teaching profession. The results revealed four different areas of concern for the participants related to methodology, self, curriculum and students. Furthermore, the participants differ slightly from their counterparts in other subjects by highlighting aspects such as professional development or the teacher-parents/guardians relationship. In addition, they often express their alignment with humanistic or constructivist pedagogical approaches while simultaneously intending to work with extrinsic motivation. I argue the impossibility of classifying their underlying music teaching philosophies within the traditional ones in the field as such proposed by Keith Swanwick, Bennett Reimer and Christopher Small. Finally, I discuss the limitations and the implications of the results for the professional world.
Política de acceso abierto tomada de: https://revistas.ufg.br/musica/about
Keywords: Investigación activa en educación; Música - Estudio y enseñanza - Suecia; Music; Teaching; Philosophy; Beliefs; Sweden